Improvement of students’ critical thinking skills through problem based learning with mind map - Asri Widowati; Purwanti Widhy Hastuti; Widodo Setiyo Wibowo (Universitas Syiah Kuala, 2017)
This research aims to improve students' critical thinking skills through the implementation of Problem Based Learning (PBL) with mind map on subjects IPA 3. This research is a classroom action research, consist of stages: Planning, Implementation, Observation and Reflection. The topics are: Sexually Transmitted Diseases in the first cycle, Living Thing and Non Living Thing Component in the second cycle, and the Electric Energy Crisis in the third cycle. Instruments used are questions and observation sheets critical thinking and observation sheets of implementation of PBL model with mind map. The results showed the implementation of syntax PBL models with mind map has been good, and the average test results show an increase and most of students achieve very good in critical thinking. Thus, it can be concluded that the application of PBL models with mind map managed to improve students' critical thinking.